2020
DOI: 10.2478/raon-2020-0070
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative radiotherapy for patients with completely resected pathological stage IIIA-N2 non-small cell lung cancer: a preferential benefit for squamous cell carcinoma

Abstract: BackgroundThe beneficial effect of postoperative radiotherapy (PORT) on completely resected pathological IIIA-N2 (pIIIA-N2) non-small cell lung cancer (NSCLC) has been a subject of interest with controversy. The aim of the study was to distinguish the clinical efficacy of PORT on lung adenocarcinoma (LADC) and lung squamous cell carcinoma (LSCC) among pIIIA-N2 NSCLC.Patients and methodsBetween October 2010 and September 2016, 288 consecutive patients with completely resected pIIIA-N2 NSCLC at Beijing Chest Hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…[ 21 ] Based on the findings of Su et al, [ 22 ] postoperative chemoradiotherapy was found to be effective in treating N2-NSCLC patients, especially those with squamous cell lung cancer. Similarly, Tian et al [ 23 ] observed that PORT was beneficial for IIIA/N2 NSCLC patients with squamous cell cancer but not for those with lung adenocarcinoma. The LNR is calculated by dividing the number of positive Lymph Nodes by the total number of Lymph Nodes sampled pathologically, and it is a prognostic metric.…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 ] Based on the findings of Su et al, [ 22 ] postoperative chemoradiotherapy was found to be effective in treating N2-NSCLC patients, especially those with squamous cell lung cancer. Similarly, Tian et al [ 23 ] observed that PORT was beneficial for IIIA/N2 NSCLC patients with squamous cell cancer but not for those with lung adenocarcinoma. The LNR is calculated by dividing the number of positive Lymph Nodes by the total number of Lymph Nodes sampled pathologically, and it is a prognostic metric.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that a number of clinicopathological factors such as age, gender, grade, T‐stage, chemotherapy and LNR, were all independent risk factors for patients with poor prognosis 15,27–29 . Notably, recent years witnessed an increase in retrospective studies to explore potential candidates with stage IIIA‐N2 disease for PORT 12,28–33 . Furthermore, it was common that the number or ratio of positive nodes was identified as a predictor of responses to PORT in previous studies 12,28,29,33,34 .…”
Section: Discussionmentioning
confidence: 99%
“… 15 , 27 , 28 , 29 Notably, recent years witnessed an increase in retrospective studies to explore potential candidates with stage IIIA‐N2 disease for PORT. 12 , 28 , 29 , 30 , 31 , 32 , 33 Furthermore, it was common that the number or ratio of positive nodes was identified as a predictor of responses to PORT in previous studies. 12 , 28 , 29 , 33 , 34 For instance, Gao et al 12 found that PORT only exhibited its role in improving survival in stage IIIA‐N2 NSCLC with PLN ≥6.…”
Section: Discussionmentioning
confidence: 99%
“…There is considerable discussion in the medical community about whether patients with pIIIA-N2 NSCLC should receive postoperative radiation. [44][45][46][47] According to some studies, patients in the high-risk group should consider and may benefit from postoperative radiation. However, clinical evidence of its benefit is required to support the claim.…”
Section: Discussionmentioning
confidence: 99%